The Reverse-Flow Facial Artery Buccinator Flap for Skull Base Reconstruction: Key Anatomical and Technical Considerations - Farzal, Zainab; Lemos-Rodriguez, Ana M.; Rawal, Rounak B.; Overton, Lewis J.; Sreenath, Satyan B.; Patel, Mihir R.; Zanation, Adam M. (Journal of Neurological Surgery Part B: Skull Base, 2015)
Objective To highlight key anatomical and technical considerations for facial artery identification, and harvest and transposition of the facial artery buccinator (FAB) flap to facilitate its future use in anterior skull base reconstruction. Only a few studies have evaluated the reverse-flow FAB flap for skull base defects.Design Eight FAB flaps were raised in four cadaveric heads and divided into thirds; the facial artery's course at the superior and inferior borders of the flap was measured noting in which incisional third of the flap it laid. The flap's reach to the anterior cranial fossa, sella turcica, clival recess, and contralateral cribriform plate were studied. A clinical case and operative video are also presented.Results The facial artery had a near vertical course and stayed with the middle (⅝) or posterior third (⅜) of the flap in the inferior and superior incisions. Seven of eight flaps covered the sellar/planar regions. Only four of eight flaps covered the contralateral cribriform region. Lastly, none reached the middle third of the clivus.Conclusions The FAB flap requires an understanding of the facial artery's course, generally seen in the middle third of the flap, and is an appropriate alternative for sellar/planar and ipsilateral cribriform defects.
Keywords: skull base reconstruction; facial artery buccinator flap; cerebrospinal fluid leak; facial artery